(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Digital Screen exposure has become a common activity in the contemporary society. There are reports that excessive screen exposures have contributed to increased frequency of migraines. Prolonged use of digital devices in evening hours may interfere with sleep, increase the severity of the visual strains, and increase the frequency and recurrence of migraines. The current study was aimed to determine the relationship between exposure to digital screens and the pattern of migraine attacks among adults. Methods: The total sample size of the study was 60 they were selected by convenience sampling method with patients diagnosed with migraine. Total of n=48(80) of these were female and remaining n=12(20%) were males. The mean age group of the cohort was 35.2 ± 9.8 years. The respondents were requested to keep a 4-week daily screen time and headache attack frequency. Baseline demographics, migraine characteristics and questionnaire scores (MIDAS, HIT-6, PSQI, PSS-10, and CVS-Q) were measured. The association between migraine outcomes and screen time was determined using spearman correlations and multivariate negative binomial regressions. Results: The overall mean total daily screen time of 7.8 ± 2.5 hours with smartphone (4.1 ± 1.8 h) and computers/laptops (3.2 ± 2.4 h) were the major sources. Average evening screen time was 1.9 ± 0.8 h. During the study, patients experienced a mean monthly migraine attack frequency of 6.2 ± 2.4 and 8.5 ± 3.1 monthly headache days. Bivariate analysis showed that the total screen time (ρ=0.42), evening screen time (ρ=0.48), CVS-Q score (ρ= 0.51) and frequency of migraine attack (p<0.01) had significant positive correlations. Regression analysis proved evening screen time (IRR 1.24; 95% CI 1.111.39 and p=0.001) and total screen time (IRR 1.09; 95% CI 1.021.16 and p=0.008) as independent predictors of migraine frequency on the condition of the covariants such as sleep quality and baseline attack frequency. Conclusions: Excessive digital screen time, particularly during the evening hours, is independently linked with an increase in the frequency of migraine attacks. The results also put emphasis on digital screen hygiene and behavioral strategies, e.g., reducing the evening screen time, and prevention strategies, including blue-light filters and frequent breaks, which can reduce the frequency of migraine attacks.